Druk gi norbu : the precious gem of Bhutan / (Acc.3942) the precious gem of Bhutan - Lam Kezang 1955-; Phuntsho, Namgyel. 1949- (Thimphu : Dorling Consultancy, 2009)
Account of 4th Bhutan King Jigme Sangye Wangchuk, b. 1955.